Removal of heavy metals by chitin: equilibrium, kinetic and thermodynamic studies - Wassila Boulaiche (Applied Water Science, 2019)
Abstract Adsorption is one of the most commonly used methods for the wastewaters treatment. In this work, we studied the impact of experimental conditions on the adsorption of heavy metals M(II) (M = Cd, Ni, Cu, Pb and Zn) in batch system using chitin obtained from crab shells. This biomaterial is selected because of its low cost, availability and efficiency. The M(II) adsorption was found to be dependent on the initial pH, contact time, initial concentration of M(II) and biomass dose. The kinetic models of Elovich, pseudo-first-order and pseudo-second-order kinetic models were successfully applied, providing the best fitting of the experimental data. The Langmuir, Freundlich, Temkin and Dubinin–Radushkevich isotherms and the thermodynamic parameters were also discussed. The adsorption capacity peaks at: 50, 47.61, 43.4, 40 and 38.46 (mg L−1) for Pb(II), Cu(II),Ni(II), Cd(II) and Zn(II), respectively. The negative free energy (∆G°) and positive enthalpy (∆H°) indicated spontaneous and endothermic adsorption.